Halfway to Cancun: The Economic Collocation of a Peasant Community in Yucatan - Brown, Denise F. (Culture, 1981)
In defining the ‘peasant’, reference is generally made to an unbalanced and inferior relationship with a larger economic, political and cultural unity. The exact nature of this relationship, however, continues to be unclear. The distinct features of the ‘dominant’ and corresponding ‘peasant’ sectors and the intricacies of their interdependence must be identified and analysed in order to reach a more complete theoretical understanding of complex societies. In this article, I examine one aspect of the economic sphere of a Mayan peasant village in Yucatan. The peasant, as consumer, plays a vital role in the marketing process, a process which is a mechanism in the dependence of the local sector on the urban industrial sector.